The Antibacterial Test of Bangle Rhizome Essential Oil (Zingiber Purpureum Roscoe) Originated from East Kalimantan Against Cutibacterium acnes and Staphylococcus epidermidis in Vitro - Christiane, Stephani; Toruan, Vera Madonna Lumban; Paramita, Swandari (Jurnal Ilmu Kesehatan, 2025)
Two bacteria, Cutibacterium acnes and Staphylococcus epidermidis, contribute to the pathophysiology of acne vulgaris and have led to resistance. Therefore, a new antibacterial agent is needed that is not resistant to both bacteria, namely the rhizome of Zingiber purpureum Roscoe (Bangle) from East Kalimantan. The purpose of this study is to examine the antibacterial activity of Zingiber purpureum Roscoe rhizome essential oil from East Kalimantan and the optimal concentration that inhibits Cutibacterium acnes and Staphylococcus epidermidis from growing in vitro. This research used a laboratory experimental study and Kirby-Bauer disc diffusion method. A posttest only control group as a study design in this research. This study used four concentrations of Zingiber purpureum Roscoe rhizome essential oil (25%; 50%: 75%; and 100%), Chloramphenicol 30μg/disk as a positive control, and tween 80 as a negative control. The result of the inhibition zone on Cutibacterium acnes was 5.6 mm (25% concentration), 5.8 mm (50% concentration), 7.5 mm (75% concentration), and 7.8 mm (100% concentration). Meanwhile, the inhibition zone on Staphylococcus epidermidis was 4.8 mm (25% concentration), 7.8 mm (50% concentration), 8.5 mm (75% concentration), and 9.1 mm (100% concentration). The results of the data analysis were p>0.05. The conclusion is that Zingiber purpureum Roscoe rhizome essential oil from East Kalimantan has an antibacterial activity that inhibits Cutibacterium acnes and Staphylococcus epidermidis from growing in vitro and optimal concentration at a concentration of 100%.